Informational support of the automated control system for baking production - Pankov, Dmitry; Kyshenko, Vasil (My University, 2018)
In order to increase the efficiency of production in the baking industry, a special role is assigned to the automation of technological processes implemented on the basis of intelligent mechanisms and modern microprocessor technology. The main reserves for improving efficiency through automation are improving the quality of baking products, the use of resource-saving technological regimes and increasing productivity of production. Taking into consideration the high lability of the raw materials characteristics, the current problem of automation in baking plants is operational complex evaluation of the quality of raw materials in real time, semi-finished products and finished products by methods of dynamic quality control. The solution of such problems is possible only on the basis of modern intellectual technologies and advanced achievements in the theory and practice of automated management. To ensure optimal management of the technological complex of bakery production, it is necessary to use a system of support and decision making based on an expert system.
Keywords: baking production; automated control system; information support; хлібопекарське виробництво; автоматизована система управління; інформаційне забезпечення; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка